Comprehensive Approach to Core Training in Sports Physical Therapy: Optimizing Performance and Minimizing Injuries - Lewis G Lupowitz (International Journal of Sports Physical Therapy)
This clinical commentary explores the significance of a comprehensive approach to core training in sports physical therapy, focusing on optimizing performance and minimizing injuries. The core, encompassing multiple regions from the scapula to the glutes and beyond, plays a vital role in athletic performance and injury prevention. The commentary provides a thorough understanding of the various "cores" in the body, highlighting their primary functions and the importance of core stability.